Intensification of rice farming: The role of mechanization and irrigation - Takeshima, Hiroyuki; Mano, Yukichi (Springer, 2023)
PART III of this volume discusses complementary strategies toward the rice Green Revolution in sub-Saharan Africa (SSA), including mechanization, irrigation, and marketing efforts to enhance demand for domestic rice. In Asia, population pressure on land and high rice prices relative to input prices induced farming intensification, while mechanization and irrigation development boosted rice productivity. However, in SSA, increased rice demand has been partly met by rice imports without adequate investments in these important technologies. This chapter reviews the available evidence on the constraints and potentials of these complementary strategies in SSA. In particular, we argue that inadequate understanding of the complementarity of each strategy with rice cultivation training may be an important reason behind low technology adoption. The remaining chapters in PART III attempt to narrow this gap and provide relevant empirical evidence. Intensive land preparation using tractors facilitates the adoption of management-intensive practices, while the provision of rice cultivation training is associated with the improved economic viability of irrigation investment. Increased demand for domestic rice is also expected to raise the returns to rice cultivation training and technology investment. The adoption of modern milling technologies improves the quality of domestic milled rice and promotes rice value-chain transformation. Local traders offer quality-based pricing that incentivizes farmers to supply high-quality paddy, while urban traders and supermarkets sell domestically produced and milled rice with brand names at a premium. In sum, the use of tractors, irrigation investment, and modern milling, combined with improved rice marketing, play critical roles that complement rice cultivation training in achieving the rice Green Revolution in SSA.